Contribution of Emotional Intelligence to Efficient Leadership. A Narrative Review - Koutsioumpa, Eftichia Maria (Technium Social Sciences Journal, 2023)
Introduction: Emotional intelligence contributes to the development of successful communication between leaders and employees and ensures good management. It is an integral part of the leader to control and regulate the well-being of his subordinates. The purpose of the present systematic review is to synthesize the available data on the role of emotional intelligence in the leadership of various domains (businesses, schools, sports teams, teams). It attempts to show emotional intelligence’s positive and direct relationship with leadership, especially with charismatic leadership. Material and method: This systematic review was carried out for 2019-2023. Criteria for inclusion of an article in the study were to be published from 2019 to 2023, to be relevant to the topic, to be published in a valid journal, to be published in the English language, to belong to the discipline of psychology, and to have open access. After a systematic and critical evaluation, seven articles were included in the study. Results: The studies addressed the role of emotional intelligence in leadership and their interaction. Transformational leadership leads people with high emotional intelligence to adapt. In addition, leadership skills training develops practical skills, assessment and problem-solving skills, communication skills, self-governance, and emotion recognition skills. Emotional intelligence plays a pivotal role in effective leadership. Leaders with high EI tend to be more transformational, make better decisions, manage stress effectively, and create cohesive team dynamics. While the relevance of EI in leadership is undeniable, future research will undoubtedly continue to refine our understanding of its nuances and applications in diverse contexts.